2004
DOI: 10.1128/aem.70.7.3821-3830.2004
|View full text |Cite
|
Sign up to set email alerts
|

Specific Response of a Novel and Abundant Lactobacillus amylovorus -Like Phylotype to Dietary Prebiotics in the Guts of Weaning Piglets

Abstract: Using 16S rRNA gene-based approaches, we analyzed the responses of ileal and colonic bacterial communities of weaning piglets to dietary addition of four fermentable carbohydrates (inulin, lactulose, wheat starch, and sugar beet pulp). An enriched diet and a control diet lacking these fermentable carbohydrates were fed to piglets for 4 days (n ‫؍‬ 48), and 10 days (n ‫؍‬ 48), and the lumen-associated microbiota were compared using denaturing gradient gel electrophoresis (DGGE) analysis of amplified 16S rRNA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
159
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(191 citation statements)
references
References 62 publications
16
159
1
4
Order By: Relevance
“…Although prebiotics like inulin may improve growth performance of young pigs, the current results did not reflect this fact. An increased growth and improved FCR together with reduction of diarrhea or loose feces as a consequence of non-digestible oligosaccharides inclusion in young pigs' diets has been reported (Konstantinov et al, 2004). However, no effect of non-digestible oligosaccharides on growth performance of young pigs were found by Houdijk et al (1999).…”
Section: Resultsmentioning
confidence: 69%
“…Although prebiotics like inulin may improve growth performance of young pigs, the current results did not reflect this fact. An increased growth and improved FCR together with reduction of diarrhea or loose feces as a consequence of non-digestible oligosaccharides inclusion in young pigs' diets has been reported (Konstantinov et al, 2004). However, no effect of non-digestible oligosaccharides on growth performance of young pigs were found by Houdijk et al (1999).…”
Section: Resultsmentioning
confidence: 69%
“…The prevalence of this species in pig faeces coincides with its use as a microbial marker of pig manure (Marti et al, 2010). Konstantinov et al (2004) demonstrated that the combination of dietary fibre and oligosaccharides present in the diet may specifically stimulate the L. amylovorus-like population along the gut of weaning pigs.…”
Section: Discussionmentioning
confidence: 84%
“…The prevalence of this species in pig faeces coincides with its use as a microbial marker of pig manure (Marti et al, 2010). Konstantinov et al (2004) demonstrated that the combination of dietary fibre and oligosaccharides present in the diet may specifically stimulate the L. amylovorus-like population along the gut of weaning pigs.The LD b-glucan caused a shift in the community whereby L. ruminis emerged after the feeding period. L. ruminis has been identified as the dominant lactic acid producing bacterium in the caecum and rectum of the pig (Jassim, 2003).…”
mentioning
confidence: 84%
“…However, molecular based profiling studies in the pig have demonstrated marked differences in microbial composition between proximal and distal intestinal locations (Konstantinov et al, 2004;Hill et al, 2005;Richards et al, 2005).…”
Section: Successional Changesmentioning
confidence: 99%